2021
DOI: 10.1080/09546634.2021.1890683
|View full text |Cite
|
Sign up to set email alerts
|

PASI 100 response rates in moderate to severe psoriasis: a systematic literature review and analysis of clinical practice guidelines

Abstract: lim AND [medline]/lim) 9 'cohort analysis' 479.192 10 ((('psoriasis'/exp OR 'psoriasis') AND ('psoriasis area and severity index' OR pasi:ti,ab)) AND ('article'/it OR 'review'/it)) AND 'cohort analysis' 183 11 (((('psoriasis'/exp OR 'psoriasis') AND ('psoriasis area and severity index' OR pasi:ti,ab)) AND ('article'/it OR 'review'/it)) AND 'cohort analysis') AND [embase]/lim NOT ([embase]/lim AND [medline]/lim) 15 12 'pasi100' 66 13 'pasi 100' 250 14 'pasi100' OR 'pasi 100' 311 15 ((('psoriasis'/exp OR 'psoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 121 publications
0
20
0
Order By: Relevance
“…Interestingly, inspection of Table 1 suggests a temporal trend for the use of more stringent PASI criteria (from 75 to 90% improvement [PASI 75 and PASI 90, respectively]), thus reflecting the advent and efficacy of biologicals ( 64 , 65 ). More recently, studies have used complete resolution of lesions (PASI 100) as an endpoint that has been met more frequently with biologicals than with conventional therapies in moderate to severe psoriasis ( 66 ). These findings suggest that PASI 100 could be a feasible target for early intervention for psoriasis.…”
Section: Assessing the Benefit Of Early Interventionmentioning
confidence: 99%
“…Interestingly, inspection of Table 1 suggests a temporal trend for the use of more stringent PASI criteria (from 75 to 90% improvement [PASI 75 and PASI 90, respectively]), thus reflecting the advent and efficacy of biologicals ( 64 , 65 ). More recently, studies have used complete resolution of lesions (PASI 100) as an endpoint that has been met more frequently with biologicals than with conventional therapies in moderate to severe psoriasis ( 66 ). These findings suggest that PASI 100 could be a feasible target for early intervention for psoriasis.…”
Section: Assessing the Benefit Of Early Interventionmentioning
confidence: 99%
“…Moreover, since the arrival of the newer class biologics (i.e. interleukin (IL)‐17 and IL‐23 inhibitors), long‐term, (near) complete skin clearance (CSC) has become reality 3,4 …”
Section: Introductionmentioning
confidence: 99%
“…In clinical trials, the novel class biologics showed superior efficacy compared to the older classes, that is, tumour necrosis alpha (TNFα) inhibitors (TNFi) and the IL‐12/23p40 inhibitor ustekinumab (UST), in both short and long term 1,3,4,9–14 . However, data from daily practice and/or registries might better reflect the real‐world effectiveness of biologics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations